Cloning and expression of Aspergillus flavus urate oxidase in Pichia pastoris - Fazel, Ramin (Springer International Publishing, 2014)
Urate oxidase is an important enzyme with therapeutic and diagnostic applications. Rasburicase is a recombinant urate oxidase enzyme approved by FDA to use in the treatment of hyperuricemia conditions. Various hosts such as Saccharomyces cerevisiae, Hansenula polymorpha and Escherichia coli have been used to express the enzyme. Today, Pichia pastoris is considered as an important host for heterologous protein expression since it has beneficial characteristics such as strong promoters, simple scale up, post translational modifications, high cell density cultivation and simple genetic manipulation. In this study, Aspergillus flavus urate oxidase gene was cloned in pPICZαA expression vector and expressed in P. pastoris. The recombinant urate oxidase was expressed in secretory form and was confirmed through RT-PCR, SDS-PAGE analysis and western blotting. The enzyme activity was determined using a colorimetric assay. A production yield of 0.43 U/ml of culture supernatant was obtained. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2193-1801-3-395) contains supplementary material, which is available to authorized users.